Functional analysis of promoter element 2 within the viral polymerase gene of an emerging paramyxovirus, Sosuga virus - Lipi Akter; Junna Kawasaki; Tofazzal Md. Rakib; Takashi Okura; Fumihiro Kato; Shohei Kojima; Kosuke Oda; Yusuke Matsumoto (Microbiology Spectrum)
ABSTRACT Paramyxovirus genomes carry bipartite promoters at the 3′ ends of both their genome and antigenome, thereby initiating RNA synthesis, which requires the viral polymerase to recognize two elements: the primary promoter element 1 (PE1) and the secondary promoter element 2 (PE2). We have previously shown that the antigenomic PE2 (agPE2) in many viruses in the Rubulavirinae subfamily is located within the coding region of the viral RNA polymerase L gene. Sosuga virus (SOSV), belonging to the Rubulavirinae subfamily, is highly pathogenic to humans, thus necessitating high-level containment facilities for infectious virus research. The use of a minigenome system permits studies of viral RNA synthesis at lower biosafety levels. Because minigenomes of negative-strand RNA viruses generally comprise only the untranslated regions, agPE2 within the L coding region—such as those found in Rubulavirinae like SOSV—is typically omitted. However, generating an SOSV minigenome that retains agPE2 led to a pronounced increase in activity, enabling a detailed examination of the role of agPE2 in SOSV replication. In many Rubulavirinae, the agPE2 not only acts as a promoter but also encodes part of the L protein, resulting in a distinct motif at the C-terminus of the L protein. We have further shown that this motif is preserved even in Rubulavirinae that no longer contain the agPE2 within the L gene.IMPORTANCEParamyxoviruses are classified into three major subfamilies: Orthoparamyxovirinae, Avulavirinae, and Rubulavirinae. All paramyxovirus genomes and antigenomes possess bipartite promoters, comprising two elements: promoter element 1 (PE1) at the 3′ end and promoter element 2 (PE2) located internally. We previously revealed that, in many Rubulavirinae, the antigenomic PE2 lies within the coding region of the viral RNA polymerase L gene. In this study, we used Sosuga virus, a member of the Rubulavirinae subfamily, to elucidate the role of antigenomic PE2 in viral replication. Because the PE2 region encodes part of the L protein, its presence leads to a distinctive motif at the C-terminus of L protein. Notably, this motif is conserved in all Rubulavirinae, including those that do not harbor the antigenomic PE2 within their L gene, indicating its importance in viral propagation.